Comparison between the long-axis/in-plane and short-axis/out-of-plane approaches for ultrasound-guided vascular catheterization: an updated meta-analysis and trial sequential analysis - Liu C; Mao Z; Kang HJ; Hu X; Jiang S; Hu P; Hu J; Zhou F (Dove Medical Press, 2018)
Chao Liu,* Zhi Mao,* Hongjun Kang, Xin Hu, Shengmao Jiang, Pan Hu, Jie Hu, Feihu Zhou Department of Critical Care Medicine, Chinese People’s Liberation Army General Hospital, Beijing, People’s Republic of China *These authors contributed equally to this work Background: A long-axis in-plane (LA-IP) approach and a short-axis out-of-plane (SA-OOP) approach are the two main approaches used in ultrasound (US)-guided vascular catheterization. However, the efficacy and safety of these approaches remain controversial. Therefore, we performed this meta-analysis to compare the two techniques in vascular catheterization. Materials and methods: Relevant studies were searched in PubMed, Embase, and the Cochrane Library databases from database inception until August 2017. Randomized controlled trials comparing a long-axis approach with a short-axis approach for US-guided vascular cannulation were selected. The RevMan software was used to analyze the results, and trial sequential analysis (TSA) was further applied to determine whether the currently available evidence was sufficient and conclusive. Results: Eleven studies met the inclusion criteria. Overall, 1,210 patients were included. The total success rate was similar between the SA-OOP and LA-IP approaches for US-guided vascular catheterization (risk ratio [RR], 1.01; 95% CI, 0.99–1.04; P=0.35; I2=48%). In the radial artery (RA; RR, 1.00; 95% CI, 0.96–1.05; P=0.88; I2=49%) and internal jugular vein (IJV; RR, 1.00; 95% CI, 0.98–1.02; P=0.99; I2=0%) subgroups, the total success rate was also similar and was confirmed by the TSA. For populations with subclavian vein (SCV) and axillary vein catheterization, the SA-OOP approach showed a benefit for first-attempt success rate. No significant differences in first-attempt success rate, cannulation times, or complications were found between the two approaches. Conclusion: Despite a similar total success rate between the SA-OOP approach and the LA-IP approach when used for RA and IJV catheterization (as confirmed by TSA), further robust well-designed trials are warranted to evaluate other outcomes. There is insufficient evidence to definitively state that the SA-OOP approach was superior to the LA-IP approach when used for SCV and axillary vein catheterization. High-quality trials are needed to confirm or refute this finding. Keywords: ultrasound guidance, long-axis in-plane, short-axis out-of-plane, vascular catheterization, radial artery, internal jugular vein